Occurrence, Diversity, and Character of Bacillaceae in the Solid Fermentation Process of Strong Aromatic Liquors - Tong, Wenhua; He, Ping; Yang, Ying; Qiao, Zongwei; Huang, Dan; Luo, Huibo; Feng, Xinjun (Frontiers in Microbiology, 2022)
Strong aromatic liquors, also called strong aromatic Baijiu (SAB) in China. It is manufactured by solid fermentation, with multi-microbe mixing and cooperative fermentation process, with Daqu as a brewing starter. Bacillaceae have specific action in food fermentation, such as soybean and wine, and more recent studies have found Bacillaceae play important roles in SAB making industry. The review described the diversity, functionality, and influence of Bacillaceae in Daqu, pit mud, Zaopei, Huangshui within making processes of SAB. Furthermore, aromatic flavor components from Bacillaceae metabolism of SAB were discussed in this review. Ultimately, the resulting improvements with deep understanding will benefit practical efforts to apply representatives of Bacillaceae in improving the quality of SAB as well as biological control of micro-ecological environment of brewing.